Paul’s Justification by Faith: Reformers’ Perspective and Implication for Theological Learning - Yee Xian Chia (Sekolah Tinggi Theologia Jaffray, 2022)
Since the Fall, man is totally depraved. Therefore, Paul insists that “a man is not justified by observing the law, but by faith in Jesus Christ.” The doctrine of Justification by Faith is one of the most important doctrines of Protestantism. Justification is the remission of sins and the imputation of Christ’s righteousness to sinners who have believed. However, the teaching of this doctrine is largely neglected today when churches do not support the three basic presuppositions in which the doctrine of Justification by Faith rests: the divine authority of Holy Scripture, the divine wrath against sin and the substitutionary satisfaction of Christ. When these truths are not supported and taught, inevitably the doctrine of Justification by Faith will be neglected. The doctrine of Justification by Faith determines whether the church stands or falls. When this doctrine is understood, believed, preached and taught, the church stands in the grace of God and is alive. On the other hand, when this doctrine is neglected, the church will fall from grace and will be in a state of darkness and death. The writer would like to reinstate the doctrine of Justification by Faith to its rightful and central place by giving an overview of Paul’s, Patristic Fathers’ and Reformers’ perspectives of justification. The doctrine of Justification by Faith must be taught in its biblical setting and its presuppositions re-established. Qualitative methods will be used in this study in the form of library research and journals.